From multi-speed to multi-stream? Recognising the motivations, processes and triggers behind party membership. (August 2020) - Power, Sam; Dommett, Katharine
A key question facing scholars of party politics is the journey engaged individuals take to becoming party members. We argue that the existing literature largely outlines one aspect – motivation. In this article, we present an alternative position: that a membership journey is only complete when a motivation, process and trigger are present. We outline this utilising a case study of the Green Party of England and Wales including previously confidential internal party documents, membership figures, elite interviews, focus group research and participant observation to provide a different means to understand membership fluctuations. We present these findings as an exploratory and inductive reinterpretation of existing debates. However, we also suggest that the findings are of interest not just in the case of the Green Party, nor the United Kingdom, but to all those who study party membership.